PENGEMBANGAN KETRAMPILAN ABAD 21 DALAM MENGHADAPI KURIKULUM MERDEKA DI PERGURUAN TINGGI - Muhamad Saiin; Rosaniya E. Rehiara; Fahrur Rozi; Hamdiana; Muhammad Rifai; Meike Negawati Kesek (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The Merdeka Curriculum introduced by the Ministry of Education and Culture of the Republic of Indonesia is an effort to prepare university graduates who are ready to face the challenges of the 21st century. 21st century skills such as critical thinking, creativity, collaboration, and communication are the keys to success in this increasingly complex era. Universities need to develop learning strategies and innovations that can encourage the development of students' 21st century skills. This paper aims to examine how universities can develop students' 21st century skills in the context of the Merdeka Curriculum. The method used is a literature study by analysing various sources related to the Merdeka Curriculum and 21st century skills. The results show that universities need to change the learning paradigm, design a competency-based curriculum, adopt an active learning model, and create a learning environment that supports the development of 21st century skills. In addition, collaboration between universities, industry, and the community is also needed to ensure the suitability of graduate competencies with needs.